Comprehensive Mapping of the Cell Response to Borrelia bavariensis in the Brain Microvascular Endothelial Cells in vitro Using RNA-Seq - Tkáčová, Zuzana; Bhide, Katarína; Mochnáčová, Evelina; Petroušková, Patrícia; Hruškovicová, Jana; Kulkarni, Amod; Bhide, Mangesh (Frontiers in Microbiology, 2021)
Borrelia bavariensis can invade the central nervous system by crossing the blood-brain barrier (BBB). It is predicted that B. bavariensis evokes numerous signaling cascades in the human brain microvascular endothelial cells (hBMECs) and exploits them to traverse across the BBB. The complete picture of signaling events in hBMECs induced by B. bavariensis remains uncovered. Using RNA sequencing, we mapped 11,398 genes and identified 295 differentially expressed genes (DEGs, 251 upregulated genes and 44 downregulated genes) in B. bavariensis challenged hBMECs. The results obtained from RNA-seq were validated with qPCR. Gene ontology analysis revealed the participation of DEGs in a number of biological processes like cell communication, organization of the extracellular matrix, vesicle-mediated transport, cell response triggered by pattern recognition receptors, antigen processing via MHC class I, cellular stress, metabolism, signal transduction, etc. The expression of several non-protein coding genes was also evoked. In this manuscript, we discuss in detail the correlation between several signaling cascades elicited and the translocation of BBB by B. bavariensis. The data revealed here may contribute to a better understanding of the mechanisms employed by B. bavariensis to cross the BBB.